1999
DOI: 10.1029/1999jd900411
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of particle nucleation: Initial results for H2SO4, H2O, and NH3 vapors

Abstract: Abstract. Particle formation in the binary H2SO4-H20 vapor system was studied at 295 K in a series of experiments employing a flow reactor. The concentration of H2SO4 was detected by chemical ionization mass spectrometry, and an ultrafine particle condensation nucleus counter was used to count the newly nucleated particles. Results yield a particle formation rate that is approximately proportional to [H2SO4] raised to the eighth power and to [H20] raised to the fifth power. The power dependencies measured here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
471
18
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(530 citation statements)
references
References 24 publications
40
471
18
1
Order By: Relevance
“…[16][17][18] The presence of ammonia (NH 3 ) can stabilize nucleating clusters, and enhance nucleation by orders of magnitude. [19][20][21][22][23][24] However, even taking into account this effect, atmospheric concentrations of H 2 SO 4 and NH 3 are often not sufficient to explain nucleation rates in the atmosphere. 23 Amines have recently been recognized as additional bases that can participate in NPF.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The presence of ammonia (NH 3 ) can stabilize nucleating clusters, and enhance nucleation by orders of magnitude. [19][20][21][22][23][24] However, even taking into account this effect, atmospheric concentrations of H 2 SO 4 and NH 3 are often not sufficient to explain nucleation rates in the atmosphere. 23 Amines have recently been recognized as additional bases that can participate in NPF.…”
Section: Introductionmentioning
confidence: 99%
“…ChemCorrespondence to: S.-H. Lee (slee19@kent.edu) ical analysis of aerosol composition also showed that newly formed atmospheric aerosol particles indeed contain ammonium (NH + 4 ) and sulfate (SO 2− 4 ) along with other components . Laboratory nucleation observations (Ball et al, 1999;Benson et al, 2009) further demonstrated that NH 3 can enhance sulfuric acid and water homogeneous nucleation (Merikanto et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Ammoniated aerosols are a dominant component of inorganic aerosol mass in both clean and urban regions (Jimenez et al, 2009). Gas-phase NH 3 measurements are crucial for understanding aerosol nucleation and new particle formation (Ball et al, 1999;Hanson and Eisele, 2002;McMurry et al, 2005;Benson et al, 2011), which facilitate long-range transport of aerosol ammonium and nitrate (Nowak et al, 2007;Pinder et al, 2008). Ammoniated sulfate aerosols also play an important role in cirrus cloud nucleation (Tabazadeh and Toon, 1998;Wang et al, 2008), and aerosol-cloud interactions have significant yet highly uncertain radiative effects on climate (Adams et al, 2001;Martin et al, 2004;Solomon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%